Estimating the returns to education in Argentina : 1992-2002 - Giovagnoli, Paula Inés (Policy research working paper, 2005)
"The authors estimate returns to schooling in urban Argentina for a 10-year period. In addition to comparable earnings functions, they also estimate the returns using quantile regression analysis to detect differences in the returns across the distribution. Over time, men in higher quantiles have higher returns to schooling compared with those in the lower quantiles. For women, returns are highest at the lowest quantile. The returns to education increased during the past decade. The authors do not rule out that increased demand for skills is driving the increasing returns over the decade. "--World Bank web site